Actualisation of Pancasila Values ​​to Prevent Corruption: Case Study of E-KTP Corruption at the Corruption Eradication Commission in Indonesia - Fieldy, Roshan; Indrawan, Rafli; Silvina, Amanda; Surendra , Septian; Hayatunnisa , Mutiara; Vijia Sheren , Nola (Borneo Novelty Publishing, 2024)
Efforts to eradicate corruption in Indonesia have been carried out in various ways, ranging from more extreme violations of the law to prevention efforts by building public awareness. However, corruption still occurs in various ways carried out by both individuals and organizations. This shows that the struggle to eradicate corruption has not been fully effective. Corruption has a significant negative impact on the nation and its citizens. Its impact can be expressed in various aspects of daily life, such as the quality of public services, social progress, and the lack of public trust in the government. Corruption can instill moral and ethical values ​​in the younger generation, which can make them more tolerant and less critical of the state. In addition, corruption damages political stability and economic stability in the Nation because it uses resources that should be used to build a strong nation. Personal interests override public interests in the administrative process, rendering bureaucracy ineffective. There are several factors that influence efforts to prevent corruption, including structural factors related to the government system, cultural factors that influence public tolerance of corruption, instrumental factors that highlight the limitations of technology and equipment, and  running well